Adopting Cleaner Production Technology and Green Supply Chain to Achieve Environmental Sustainability: An Applied Study - Ali Atta Obaid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research aims to examine the impact of integrating cleaner production practices with green supply chain technologies as a comprehensive approach to achieving environmental sustainability. The study highlights that cleaner production and green supply chain management represent advanced, innovative strategies that have emerged as a response to the growing environmental challenges caused by the rapid expansion and diversification of industrial activities. These technologies are not only environmentally oriented but also carry significant economic implications for organizations. The findings emphasize that adopting cleaner production involves minimizing waste generation, improving production efficiency, and ensuring that processes are designed to have minimal adverse effects on the environment. On the other hand, green supply chain technologies focus on integrating environmental thinking into every stage of the supply chain—ranging from product design, material sourcing, and manufacturing processes to logistics, product delivery, and end-of-life management. The study concludes that the synergy between these two approaches provides multiple benefits. From an environmental perspective, they contribute to reducing carbon emissions, particularly from fuel-powered machinery and transportation systems. They also promote the rational use of resources, including energy, water, and raw materials, thereby helping to preserve natural resources for future generations. From an economic perspective, their implementation leads to reduced operational costs by enhancing efficiency, decreasing waste disposal expenses, and optimizing resource usage. Furthermore, the integration of cleaner production and green supply chain technologies supports compliance with environmental regulations and enhances the corporate image of economic units, enabling them to gain competitive advantages in increasingly eco-conscious markets. Overall, the research affirms that these practices are essential tools for confronting and mitigating the environmental pollution challenges of modern industries, while simultaneously fostering sustainable economic growth and long-term environmental protection.